2016
DOI: 10.1186/s12943-016-0495-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the dopamine transporter SLC6A3 as a biomarker for patients with renal cell carcinoma

Abstract: BackgroundClear cell renal cell carcinoma (ccRCC) is among the most common human malignancies.MethodsIn order to provide better understanding of the molecular biology of ccRCC and to identify potential diagnostic/prognostic biomarker and therapeutic targets, we utilized a microarray to profile mRNA expression of corresponding normal and malignant renal tissues. Real-time PCR, Western Blot and immunohistochemistry were applied to study the expression of candidate biomarkers. ccRCC cell lines were treated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 33 publications
7
51
0
Order By: Relevance
“…(36,38,40) Norepinephrine was recently shown to inhibit the migratory ability of pancreatic cells(41) while as mentioned earlier, beta-adrenergic receptor blockade is also associated with improved outcomes. (6,42-44) Recent work also found that the dopamine transporter inhibitor, sertraline, induced cell death in renal cell carcinoma,(45) data that collectively implicate catecholamine biology in carcinogenesis. (32,33)…”
Section: Discussionmentioning
confidence: 99%
“…(36,38,40) Norepinephrine was recently shown to inhibit the migratory ability of pancreatic cells(41) while as mentioned earlier, beta-adrenergic receptor blockade is also associated with improved outcomes. (6,42-44) Recent work also found that the dopamine transporter inhibitor, sertraline, induced cell death in renal cell carcinoma,(45) data that collectively implicate catecholamine biology in carcinogenesis. (32,33)…”
Section: Discussionmentioning
confidence: 99%
“…Some subunits of the electron transport chain have been linked to RCC before: NDUFA4 expression is decreased in ccRCC and may predict unfavorable outcome following nephrectomy. 9 In contrast, NDUFA4L2, a paralogue of NDUFA4, is upregulated in RCC 10,11 and altered gene expression is associated with a poor prognosis. 11 The aim of this study was to develop a better understanding of the expression of the mitochondrial complex I subunits and to determine whether some subunits may have the potential to be used as a new biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…deregulated oxygen sensing is characterized by VHL/ HIF pathway alterations with subsequent upregulation of HIF-responsive genes and glucose transporters allowing the reliance on aerobic glycolysis [24]. We earlier reported dysregulation of the electron transport chain subunit NDUFA4 [25] and its paralogue NDUFA4L2 [26], and demonstrated an prognostic relevance of NDUFA4 [25]. There is evidence for an decreased expression level of the complex III in RCC [6,27] leading to decreased activity of the electron transport chain [27].…”
Section: Discussionmentioning
confidence: 99%
“…UQCRFS1 and UQCRC1 expression was further investigated in RCC, oncocytoma and benign renal tissue using a tissue microarray (published in [26]). Paraffin sections were cut at 5 μm thickness, deparaffinized using xylene and rehydrated in graded ethanol.…”
Section: Immunohistochemistrymentioning
confidence: 99%